Pattern of Admission and Outcome in a Neonatal Intensive Care Unit (NICU) of a Tertiary Care Hospital in Dhaka, Bangladesh (Anwer Khan Modern Medical College Journal, 2019)
Background: The neonatal period is a highly vulnerable time for an infant completing many of the  physiologic adjustments required for life outside the uterus. As a result, there are high rates of morbidity  and mortality. To reduce morbidity and mortality it is essential to know the neonatal disease pattern.  Neonatal disease pattern changes from time to time and place. Analyzing the neonatal admission pattern  helps the policy makers to make the better strategies and health care givers to serve better.Objectives: This study aimed to determine the disease patterns and outcome of patients admitted to the  Neonatal Intensive Care Unit (NICU) of Anwer khan Modern Medical College Hospital, a tertiary care  hospital in Dhaka, between January 2017 to December 2018.Methods: Retrospective data from the medical records of all neonates admitted during the study period  were reviewed and analyzed for age, weight, sex, reason for admission, duration of hospital stay,  diagnosis and final outcome.Results: The total number of neonates admitted during the study period was 262; 164 were male (62.6%), and  98 were female (37.4%). A total of 223 patients (85.12%) wereborn in the hospital while 39 (12.88%) were  born at home. The majority were admitted during the first 48 hours of life (72.2%). A total of 5 patients (2%)  weighed